Pengaruh IPTIK, Infrastruktur, dan Kemiskinan Terhadap Disparitas Pendapatan di Kawasan Timur Indonesia - Ulfa Auliandari; Muhammad Anshari (Universitas Negeri Padang, 2026)
This study was motivated by the high income disparities among regions in Eastern Indonesia (KTI), which require serious attention. Using panel data regression analysis covering 17 provinces in KTI from 2015 to 2024, this study aims to examine how IPTIK, infrastructure, and poverty influence income disparities. Based on the results of testing the best model, the most appropriate model is the Random Effects Model (REM). Findings in this study indicate that IPTIK and water infrastructure significantly reduce income disparities. On the other hand, poverty has a positive and significant effect on increasing income disparity. Meanwhile, road infrastructure was not found to have a significant impact on income disparity. However, simultaneously, the variables of ICT, infrastructure, and poverty all influence income disparity in Eastern Indonesia. Based on these results, policies are needed that focus on equitable access to ICT, infrastructure, and poverty alleviation to reduce income disparity in Eastern Indonesia.